The Use of Cohesive Devices and Factors Influence Unsuccessful Coherence in Community-Based Tourism Text - Indah Puspitasari; Tri Wahyu Setiawan Prasetyoningsih (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
As a complex process, writing is always interesting to be discussed. One of the students' biggest problems in writing is in maintaining coherence. Coherence is a systemic model to unify some elements to become good writing. This article aims to identify the most cohesion type used by the students and factors that influence the unsuccessful coherence of the text. This is a descriptive qualitative research. The data were obtained by collecting descriptive text written by thirteen English Diploma Program students. The unit of analysis in this study is a community –based tourism text which describes tourism villages in Banyumas Regency, Indonesia. The writers take Community-Based Tourism (CBT) as the unit of analysis because the government right now is developing CBT in many areas in Indonesia. As an important stakeholder, the University must prepare the students to write good descriptions of CBT. The result of this study shows most of the students use reference, reiteration, and conjunction in their writing but they have very minimal use of ellipsis, substitution, and collocation. The writers found that some of the students' sentences have successful integration, but some have not successful integration. There are several factors influence unsuccessful integration. Those are students' prior knowledge, inappropriate use of cohesive devices, and illogical sequence. Finally, we can conclude that the students need more guidance and knowledge of using effective writing, cohesive devices and logical sequence.